Evaluation of Fecal Elastase and Serum Cholecystokinin in Dogs with a False Positive Fecal Elastase Test - J.M. Steiner; J.F. Rehfeld; N. Pantchev (Journal of Veterinary Internal Medicine, 2010)
Abstract Background An assay for the measurement of pancreatic elastase in dog feces has been introduced. Hypothesis/Objectives The goal of this study was to evaluate the rate of false-positive fecal-elastase test results in dogs with suspected exocrine pancreatic insufficiency (EPI) and to assess serum cholecystokinin (CCK) concentrations in dogs with a false positive fecal elastase test result. Animals Twenty-six fecal and serum samples from dogs suspected of EPI, for which samples had been submitted to a commercial laboratory (Vet Med Labor) for analysis. Methods Prospective study. Serum trypsin-like immunoreactivity (TLI) was measured in 26 dogs with a decreased fecal elastase concentration of <10 μg/g feces. Serum CCK concentrations were measured in 21 of these dogs. Results Of 26 dogs with a decreased fecal elastase concentration, 6 (23%) had serum TLI concentrations within or above the reference range. Serum CCK concentrations were significantly higher in dogs with a true positive fecal elastase test result (median: 1.1 pmol/L; range: 0.1–3.3 pmol/L) than in those with a false positive fecal elastase test result (median: 0.1 pmol/L; range: 0.1–0.9 pmol/L; P value = .0163). Conclusions and Clinical Importance The rate of false positive fecal elastase test results was high in this group of dogs, suggesting that diagnosis of EPI must be confirmed by other means. The decreased CCK concentration in dogs with a false positive fecal elastase test result could suggest that false positive results are because of decreased stimulation of exocrine pancreatic function caused by other conditions.